Efisiensi Usahatani Cabai Rawit dengan Teknologi Irigasi Tetes di Kabupaten Ciamis - Suci Nurianti; Candra Nuraini; Abdul Mutolib (Universitas Galuh, 2026)
Ciamis Regency is one of the bird’s eye chili pepper producing areas in West Java. Although this chili pepper productivity in Ciamis Regency is still relatively low, indicating that optimal farming efficiency has not yet been achieved. One of the main problems is the inefficient use of inputs, especially water. Therefore, the application of drip irrigation is considered to have the potential to improve the technical, allocative, and economic efficiency of chili pepper farming. This study aims to analyze production factors that affect chili pepper production, analyze technical inefficiency, and measure the level of technical, allocative, and economic efficiency in chili pepper farming with the application of drip irrigation. The research was conducted from June-September 2025 using a descriptive quantitative approach with a census method on 55 chili pepper farmers who use drip irrigation. Data analysis was performed using SFA with the Cobb-Douglas production function. The results of the study indicate that mulch and stakes have a positive and significant effect, while the factors of land area, manure, NPK fertilizer, lime, and drip irrigation have a positive but insignificant effect. Farmer education and experience reduce technical inefficiency, while family size increases it. Factors affecting production costs include production, manure, NPK fertilizer, pesticides, stakes, drip irrigation, and labor, which have a positive effect on cost increases. The average technical efficiency value was 0.83, allocative efficiency was 0.90, and economic efficiency was 0.74, indicating that drip irrigation is not yet fully economically efficient and still has opportunities for improved chili papper production performance.